Clinical outcomes of sildenafil application in patients of poor endometrial development - Meiling Guo; Yuchen Yan; Jianan Lv; Hua Xin; Wei Zhou; Na Yu; Mingdi Xia; Jing Li; Qian Zhang; Junhao Yan (Gynecology and Obstetrics Clinical Medicine, 2022)
Objective: To determine whether sildenafil has an effect on pregnancy outcomes in patients with poor endometrial development. Methods: This study included 472 infertility patients who underwent in vitro fertilization/intracytoplasmatic sperm injection and frozen-thawed embryo transfer (IVF/ICSI-FET) and subsequently suffered from poor endometrial development during hormone replacement cycle (HRC) from April 2017 to July 2019. The patients were divided into two groups: the sildenafil group (n ​= ​88) and the control group (n ​= ​384). We analyzed endometrial thicknesses and types on endometrial transformation day, as well as pregnancy outcomes after FET (biochemical pregnancy, clinical pregnancy, early abortion, late abortion, and live birth rates) between the two groups. Results: After adjusting for confounding factors, we found no significant differences in endometrial thicknesses and types on endometrial transformation day between the sildenafil group and the control group (0.79 ​± ​0.08 vs 0.81 ​± ​0.09, P ​= ​0.144; 79.76% vs83.87%, P ​= ​0.402). There were also no statistically significant differences in biochemical pregnancy rate (75.0% vs 76.8%, P ​= ​0.892), clinical pregnancy rate (59.09% vs 69.53%, P ​= ​0.087), early abortion rate (17.31% vs 14.61%, P ​= ​0.557), late abortion rate (3.85% vs 4.49%, P ​= ​0.859), or live birth rate (45.45% vs 55.47%, P ​= ​0.101) between the two groups. In subgroup analysis, the application of sildenafil was unable to improve endometrial thickness (group one: 0.80 ​± ​0.08 ​cm vs 0.82 ​± ​0.08 ​cm; group two:0.78 ​± ​0.08 ​cm vs 0.80 ​± ​0.10 ​cm; group three:0.75 ​± ​0.11 ​cm vs 0.77 ​± ​0.08 ​cm, p ​> ​0.05) and type endometrium on transformation day (group one: 78.57% vs 86.78%; group two: 80.65% vs 77.78%; group three: 81.82% vs 83.78%, p ​> ​0.05). Moreover, sildenafil use was not closely associated with clinical pregnancy outcomes, clinical pregnancy rate, early abortion rate, late abortion rate, and live birth rate (p ​> ​0.05). Conclusions: Sildenafil did not benefit endometrial development and pregnancy outcomes in patients with poor endometrial development during the hormone replacement cycle.